Niveles de contenido ruminal en ensilaje de pasto Panicum maximum cv. Mombaza y valoración bromatológica en cuatro tiempos de conservación. - Olvera Sánchez, Orlando Guillermo (2015)
Levels of rumen contents were evaluated in silage grass Panicum maximum cv. Mombaza and valuation bromatological four storage times. Fieldwork was conducted at the Technical University of Cotopaxi at the Experimental Farm "La Playita" Canton La Mana, Cotopaxi Province. (WGS 84 Location: Latitude S 0° 56' 27" W Longitude 79° 13' 25", height 220 meters), lasted 112 days. Hydrogen potential varies opening time treatment (Panicum Mombaza + CR 0%) shows an acidic pH at 28 days (5.89) and neutral after 84 days (7.12); treatment (Panicum Mombaza + 6% CR) shows an acidic pH at 56 days (6.62) and treatment (Panicum Mombaza CR + 12%) shows an acidic pH at 112 days (5.97). The temperature was below 35 °C, averaging between 27.0 °C to 32.0 °C (x = 29.5 °C). Dry matter percentage varies according to the opening times: at 28 days of treatment (Panicum Mombaza + CR 0%) reached 48.49%; 84 days of treatment (Panicum Mombaza + CR 6%) is higher with 64.72% at 56 and 112 days of treatment (Panicum Mombaza + CR 12%) is higher with 54.93% and 66.45%. Vsalorar bromatologías to the protein at 28 days it provides the greatest percentage treatment (Panicum Mombaza CR + 12%) 9.10%; 56 days is better treatment (Panicum Mombaza + CR 12%) 11.47%; 84 days of treatment (Panicum Mombaza + CR 6%) is higher with 8.38% and 112 days of treatment (Panicum Mombaza + CR 0%) is higher with 8.85%.